The Growth of Kiwi Shoot (Actinidia deliciosa) on Various Kinds of Gelling Agents - Mardiana Mardiana; Zainuddin Zainuddin; Mahfudz Mahfudz; Hawalina Hawalina (Universitas Tadulako, 2018)
Kiwi fruit takes about 25 weeks from flower bloom until it reaches physiological maturity, so the time required to produce kiwi seeds from seeds in large quantities and uniform is very long. Tissue culture is one method that can be used to obtain a lot of kiwi seeds and uniforms with large quantities in a faster time. The purpose of this study was to examine various types of media compaction materials for the growth of kiwi shoots in vitro. This study was prepared based on Completely Randomized Design (RAL) with 5 treatments and repeated 4 times so that there were 20 experimental units, each experiment using 2 explants so that there are 40 eksplan. The treatments were: MA 1: Agar Swallow Globe 8 g / l, MA 2: Agar Swallow Globe 4 g / l + Agar Nutrijell 4 g / l, MA 3: Agar Swallow Globe 4 g / l + Agar Nutrijell 5 g / l, MA 4: Phytagel 2.2 g / l, MA 5: Agar Nutrijell 11 g / l. Observation variables are When shoots appear, Number of shoots, number of leaves, Number of Roots, number of root hair. The results showed Swallow Globe 4 g / l + Agar Nutrijell 4 g / l treatment gave the highest average number of shoots, the highest number of leaves and roots, this proved that the combination of Swallow Globe and Nutrijell agar gave a good condition for shoot growth kiwi plant.